2024
DOI: 10.1038/s41698-023-00488-4
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the heterogeneity of colorectal cancer consensus molecular subtypes using spatial transcriptomics

Alberto Valdeolivas,
Bettina Amberg,
Nicolas Giroud
et al.

Abstract: The consensus molecular subtypes (CMS) of colorectal cancer (CRC) is the most widely-used gene expression-based classification and has contributed to a better understanding of disease heterogeneity and prognosis. Nevertheless, CMS intratumoral heterogeneity restricts its clinical application, stressing the necessity of further characterizing the composition and architecture of CRC. Here, we used Spatial Transcriptomics (ST) in combination with single-cell RNA sequencing (scRNA-seq) to decipher the spatially re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…Among desert-enriched genes, we retrieved the glucose transported GLUT10 (encoded by SLC2A10) and the Wnt pathway inhibitor NKD1, which showed preferential expression in tumor cells and fibroblasts (figure 5B-D and online supplemental figure S6B). By using publicly available spatial transcriptomics data in CRC (Valdeolivas et al 46 and Wu et al 2022 45 ), we confirmed an enrichment in NKD1 expression in CD8-desert as compared with CD8high tumor areas. In addition, we observed the strongest expression of LAMP5 in the sample showing CD8 infiltration in the stromal area only, in line with LAMP5 being excluded-enriched (online supplemental figure S6C).…”
Section: Both Cd8+ T Effector-associated and Non-immune-expressed Gen...supporting
confidence: 62%
See 1 more Smart Citation
“…Among desert-enriched genes, we retrieved the glucose transported GLUT10 (encoded by SLC2A10) and the Wnt pathway inhibitor NKD1, which showed preferential expression in tumor cells and fibroblasts (figure 5B-D and online supplemental figure S6B). By using publicly available spatial transcriptomics data in CRC (Valdeolivas et al 46 and Wu et al 2022 45 ), we confirmed an enrichment in NKD1 expression in CD8-desert as compared with CD8high tumor areas. In addition, we observed the strongest expression of LAMP5 in the sample showing CD8 infiltration in the stromal area only, in line with LAMP5 being excluded-enriched (online supplemental figure S6C).…”
Section: Both Cd8+ T Effector-associated and Non-immune-expressed Gen...supporting
confidence: 62%
“… 35 To explore the spatial distributions of individual genes, publicly available 10×Visium data from CRC 45 were reprocessed as described previously. 46 …”
Section: Methodsmentioning
confidence: 99%
“…Standardization of modeling methodologies, validation of predictive algorithms, and addressing the dynamic nature of tumor biology remain critical hurdles. Collaborative efforts between computational scientists, bioinformaticians, and experimental researchers are essential to bridge the gap between computational predictions and experimental validations, ensuring the reliability and reproducibility of precision nanomedicine strategies. , …”
Section: Future Directions and Emerging Technologiesmentioning
confidence: 99%
“…Collaborative efforts between computational scientists, bioinformaticians, and experimental researchers are essential to bridge the gap between computational predictions and experimental validations, ensuring the reliability and reproducibility of precision nanomedicine strategies. 233,234…”
Section: Future Directions and Emerging Technologiesmentioning
confidence: 99%